Heterogeneous Beliefs and Risk-Neutral Skewness - Friesen, Geoffrey C.; Zhang, Yi; Zorn, Thomas S. (Journal of Financial and Quantitative Analysis, 2012)
This study tests whether belief differences affect the cross-sectional variation of risk-neutral skewness using data on firm-level stock options traded on the Chicago Board Options Exchange from 2003 to 2006. We find that stocks with greater belief differences have more negative skews, even after controlling for systematic risk and other firm-level variables known to affect skewness. Factor analysis identifies latent variables linked to risk and belief differences. The belief factor explains more variation in the risk-neutral skewness than the risk-based factor. Our results suggest that belief differences may be one of the unexplained firm-specific components affecting skewness.